PRAKONSENTRASI DAN ANALISIS ION KADMIUM BERBASIS FLOW INJECTION ANALYSIS - Uswatun Hasanah; - Rusnadi; Bachri Amran (Universitas Pakuan, 2015)
CD-imprinted polymers (Cd-IPs) have been synthesized and retensinya properties have been studied for the pre concentration and analysis of cadmium concentration at the level of µ g L-1berbasis technique of flow injection analysis (FIA). This procedure is based on the retention of ions Cd (II) on Cd-IPs are synthesized. Retention cadmium ions can elution quantitatively with a solution of nitric acid directly onto the nebulizer system for atomic absorption spectrometer. The retention capacity of the Cd-IPs acquired for 20.10 mg g-1pada pH optimum and shows a quick retention kinetics. Analytical parameters such as retention capacity, the volume of the sample, the concentration and volume of eluen have been evaluated to obtain a good analytical performance. The system being developed makes it possible to analyze 15 samples per hour, with a limit of detection of the 8 µ g L-1. For the concentration of 50 μg L-1 has obtained precision values expressed as percent relative standard deviation of 1.6 (n = 5). A method of analysis that was developed has been used for the determination of cadmium in river water samples Cidurian, West Java, Indonesia with satisfactory results. Key words: consentration, analyzing miniscule, cadmium, FIA